2021
DOI: 10.3390/economies9030101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Institutional Support on Export Performance

Abstract: This paper examines institutional support (financial and marketing support) on export-oriented firms’ performance or so-called born globals. We develop a model to address how financial and marketing support can help young entrepreneurial firms to overcome the liability of newness and smallness in gaining competitive capabilities. Using a quantitative method, data were collected from 217 manufacturers and service sectors in Malaysia, an emerging Southeast Asian market. The results suggest that government assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…Finally, Catanzaro and Teyssier [30] indicate that export promotion programs might be linked to the development of export capabilities as well as the adoption of risk management methods. The study is also in line with the result of Mata et al [31], who indicated that finance and marketing assistance might aid young entrepreneurial enterprises in overcoming the vulnerability of newness and smallness in acquiring competitive export capacities. To conclude with a discussion, the export promotion programs have a significant impact on export competitiveness.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Finally, Catanzaro and Teyssier [30] indicate that export promotion programs might be linked to the development of export capabilities as well as the adoption of risk management methods. The study is also in line with the result of Mata et al [31], who indicated that finance and marketing assistance might aid young entrepreneurial enterprises in overcoming the vulnerability of newness and smallness in acquiring competitive export capacities. To conclude with a discussion, the export promotion programs have a significant impact on export competitiveness.…”
Section: Discussionsupporting
confidence: 90%
“…For this result, the study corresponds to the study carried out by Njinyah [29], who found the export policy from the government did not have a direct effect on export performance from both financial and non-financial perspectives, including the increased scale of business, return on investment, profit growth, and relationship with the stakeholder. In addition, the study is also consistent with Mata et al [31], indicating that competitive capabilities play a significant role in mediating the relationship between marketing support from related institutions and the export performance of the enterprises. Lastly, the study is supported by Catanzaro and Teyssier [30], who also implied that export capabilities play a crucial role in the mediation between export promotion programs offered by the government and the international performance of the small and medium businesses.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Micro-manufacturing businesses have a sales turnover of less than RM 250,000, small enterprises have a sales turnover of between RM 250,000 and RM 10,000,000, and medium-sized businesses have a sales turnover of between RM 10,000,000 and RM 250,000,000. A sales turnover of less than RM 200,000 is recorded in the microservice sector, while that of medium-sized enterprises ranges from RM 200,000 to one million, and that of large businesses ranges from one million to five million ringgits (RM 5,000,000) (Mata, Falahat, Correia, & Rita, 2021). Nigeria uses the following criteria for SMEs: Micro-enterprises are those with fewer than 10 employees and annual revenues of less than ₦ 5,000,000.00; small businesses have between 10 and 49 employees with an annual turnover that generally ranges from ₦ 5.000.000 to ₦ 49.000.000; and medium-sized enterprises have between 50 and 199 employees and an annual turnover ranging from ₦ 50.000.000 to ₦ 499.000.000 (Agwu, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%